Extrusion parameters and physical properties of sorghum-based dog food diets designed for a digestibility study - Stubbs, Miranda E.; Beyer, R. Scott; Aldrigh, Gregory; Alavi, S. (My University, 2018)
The objective of this experiment was to study the impact of raw material particle size and thermal energy intensity in extrusion processing of sorghum-based dog food diets on the physical properties of the kibbles. The diets were designed for a future digestibility and nutrient bioavailability study based on a broiler model. A maintenance adult dog food diet was created that also met the requirements for broilers, with the long-term goal of studying the growth of broilers fed sorghum-based diet as compared to a corn control diet. The sorghum-based diets were ground to pass through either a 0.51mm (0.02”) or a 1.65mm (0.065”) screen. In total, there were 5 extrusion treatments, based on a 2X2 factorial design for the sorghum-based diets (two thermal intensities corresponding to preconditioner downspout temperatures of 67-68 and 97-99°C and two particle sizes corresponding to an average of 471 and 497 microns) plus the corn-based control corresponding to higher raw material average particle size and processed at high thermal intensity. Extrusion in-barrel moisture ranged between 32-33% wet basis. Extrusion thermal energy intensity varied from 128 kJ/kg (low thermal) to 185 kJ/kg (high thermal) depending on steam input into the preconditioner. The specific mechanical energy ranged between 121-193 kJ/kg. Bulk density of kibbles increased from 280 g/L to 312 g/L with increase in particle size, because the expansion decreased as surface area to volume ratio of particles decreased. Bulk density also increased as thermal energy decreased. Hardness of kibbles was impacted by both particle size and thermal energy. Dog palatability data indicated the high thermal energy diets were preferred over the low thermal, with the former approached by dogs first in four times out of five observations and also consumed four times more.
Keywords: Fall 2018